Coastline Change along Pebuahan Beach in Jembrana Bali - Muhammad Maheswara, Aryasatya; Ni Nyoman, Pujianiki (INTI International University, 2024)
Monitoring changes in coastlines over large areas will be more efficient using satellite imagery rather than conducting field surveys. This research aims to measure the coastline transformation that occurred over a period of time at Pebuahan Beach in Jembrana Regency. This research uses the Digital Shoreline Analysis System (DSAS) program. Ex situ data for 2004 and 2019 obtained from Landsat satellite imagery was used in this research. When compared coastline between 2004 and 2019, there was more extensive abrasion, reaching 300,577.17 m2, while the accretion that occurred only reached 159,697.67 m2. The cause of abrasion at Pebuahan Beach is sediment transport which tends to leave the beach to the west and sediment supply is trapped due to obstruction at the Pengambengan Port.